2021
DOI: 10.1186/s40942-021-00348-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of silicone oil tamponade on retinal layers and choroidal thickness in patients with rhegmatogenous retinal detachment: a systematic review and meta-analysis

Abstract: Background To evaluate the effects of intravitreal silicone oil (SO) on the retinal and choroidal thickness in eyes with rhegmatogenous retinal detachment (RRD). Methods A literature search was performed in Web of Science, Scopus, ProQuest, Embase, Clinical Key, Science Direct, Cochrane Library, and Springer, as well as Persian databases, including IranDoc, MagIran, SID, MOH thesis, and MOH articles until June 2020. Two reviewers independently sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
(114 reference statements)
1
8
0
Order By: Relevance
“…Our data on central retinal thickness changes were also in keeping with previous data, that have been reviewed by Ghanbari et al: While central macular thickness reduces due to SO filling after retinal detachment repair, this effect is reversible, and CRT increases after SO removal [5]. Our data support this as CRT increases significantly after SO removal in our cohort.…”
Section: Kubicka Et Al Showed Long Term Effects On the Retinal Microp...supporting
confidence: 92%
See 2 more Smart Citations
“…Our data on central retinal thickness changes were also in keeping with previous data, that have been reviewed by Ghanbari et al: While central macular thickness reduces due to SO filling after retinal detachment repair, this effect is reversible, and CRT increases after SO removal [5]. Our data support this as CRT increases significantly after SO removal in our cohort.…”
Section: Kubicka Et Al Showed Long Term Effects On the Retinal Microp...supporting
confidence: 92%
“…Central retinal thinning might be caused by various factors like mechanical stress on the inner retinal layers, inflammatory mechanisms, toxicity on the internal limiting membrane or hydrophobicity of the oil that alters the retinal environment. Luckily, these effects seem to be short term and reversible to a large extent and is dependent on the duration of SO filling [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our OCT imaging analysis showed that there is no evidence for central macular thinning with DensironXTRA compared to the contralateral eye without RRD as well as with DensironXTRA in situ versus after its removal. A meta-analysis conducted by Ghanabri et al suggested that retinal thinning occurs with silicone oil tamponade and that silicone oil is associated with a greater degree of thinning compared to gas tamponades 36 . There is conflicting evidence whether visual acuity is affected by retinal thinning 36 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Retinal nerve fibre layers of the optic nerve head have also been described as prone to thinning during SO tamponade [ 8 ]. Changes have also been recorded in the choroid’s subfoveal region regarding its thickness reduction [ 9 ]. During silicon oil tamponade, perfusion is reduced in the macular area, and foveolar avascular zone (FAZ) extension occurs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%